Ultrasound Guided Therapeutic Excisional Vacuum Assisted Biopsy in Breast Fibroadenomas - KAYA, HANDAN; BUĞDAYCI, ONUR (AVES, 2017)
Objective: The aim of this study was to evaluate the performance of ultrasound (US) guided Vacuum Assisted Biopsy (VAB) in the therapeutic excision of breast fibroadenomas. Materials and Methods: Patients who underwent excisional US guided VAB of their fibroadenomas between December 1999-May 2001 were retrospectively evaluated. Seventy-eight patients with BI-RADS category 3 and 4a lesions (one lesion per patient) with a maximum diameter smaller than 3 cm were enrolled in the study. Fifty-one of those were diagnosed with fibroadenoma. Biopsies were performed with a 11G needle using the Mammotome (Johnson & Johnson, New Jersey, USA) vacuum biopsy device. Patients were followed up with US for three years. Follow-ups were done semiannually in the first year and annually afterwards. Results: Ten patients (19%) were found to have residual lesions in the first week after the biopsy. Additional eight patients (15%) were found to have residual-recurrent lesions in their annual follow up. However, none of these eight lesions demonstrated growth during the three year follow-up. The initial size of the FA was not found to be significantly different between the lesions which were completely excised with no residue or recurrence and those which were not (p>0.05). Conclusion: The VAB method for the therapeutic excision of small FAs or other benign lesions is practical and easily tolerated by patients. Lesions smaller than 3 cm should be preferred for VAB. A multidisciplinary clinical environment is necessary for each step of the treatment.
Keywords: Fibroadenoma; needle biopsy; image-guided biopsy; ultrasonography; SYSTEM; LESIONS